2011
DOI: 10.1007/s12010-011-9206-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Refolding of Triosephosphate Isomerase from L. donovani

Abstract: The triosephosphate isomerase of Leishmania donovani (LdTIM) was expressed at high level in Escherichia coli. The TIM gene was cloned in expression vector pET-23(a) with C-terminal 6× His tag fused in frame, and expressed as a 27.6-kDa protein in E. coli as inclusion bodies. The recombinant LdTIM from E. coli lysate was solubilized in 6 M guanidine hydrochloride and purified by Ni-NTA chromatography. In the present study, the effect of bovine serum albumin on the reactivation of TIM was investigated. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…This competition induces free hyaluronidase resulting in a large increase in the hydrolysis rate [55]. Several research groups have reported that serum proteins are able to enhance hyaluronidase activity and are sometimes required to detect the presence of hyaluronidases [55], [56], [57].…”
Section: Discussionmentioning
confidence: 99%
“…This competition induces free hyaluronidase resulting in a large increase in the hydrolysis rate [55]. Several research groups have reported that serum proteins are able to enhance hyaluronidase activity and are sometimes required to detect the presence of hyaluronidases [55], [56], [57].…”
Section: Discussionmentioning
confidence: 99%